Files cryptography based on one-time pad algorithm - Ahmad Mohamad Al-Smadi; Ahmad Al-Smadi; Roba Mahmoud Ali Aloglah; Nisrein Abu-darwish; Ahed Abugabah (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The Vernam-cipher is known as a one-time pad of algorithm that is an unbreakable algorithm because it uses a typically random key equal to the length of data to be coded, and a component of the text is encrypted with an element of the encryption key. In this paper, we propose a novel technique to overcome the obstacles that hinder the use of the Vernam algorithm. First, the Vernam and advance encryption standard AES algorithms are used to encrypt the data as well as to hide the encryption key; Second, a password is placed on the file because of the use of the AES algorithm; thus, the protection record becomes very high. The Huffman algorithm is then used for data compression to reduce the size of the output file. A set of files are encrypted and decrypted using our methodology. The experiments demonstrate the flexibility of our method, and it’s successful without losing any information.